Representasi Penegakan Hukum Terhadap Kasus Pelecehan Seksual Dalam Film “Officer Black Belt” - Yazmine Salsabilah Putri Indah Sari; Asriyani Sagiyanto; Fajar Diah Astuti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study focuses on the representation of law enforcement in sexual harassment cases as depicted in the film Officer Black Belt. The film is noteworthy as it addresses a relevant social issue, namely the monitoring of former sex offenders in South Korea. This research applies a descriptive qualitative method with Charles Sanders Peirce’s semiotic analysis, which emphasizes three main components: Sign, Object, and Interpretant. Data were collected through in-depth observation of the film. The findings reveal that Officer Black Belt represents law enforcement through visual symbols, the role of legal authorities, and the narrative of monitoring sexual offenders. The representation highlights the use of electronic ankle bracelets as a monitoring tool, while also exposing their limitations. Furthermore, the film potrays the human side of victims and the challenges faced by officers in maintaining public safety. Therefore, this study concludes that film serves not only as entertainment but also as a medium of social critique that can raise public awareness of sexual harassment issue and the urgency of more effective law enforcement.